1974
DOI: 10.1111/j.1365-2265.1974.tb03290.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Gland Enlargement in Acromegaly

Abstract: SUMMARY Three patients with active acromegaly and salivary gland enlargement are described. Detailed studies of flow rate, the biochemistry of the saliva from both the parotid and submandibular salivary glands, sialography and isotope scanning of the glands showed no significant abnormality in function. The literature is reviewed and it would appear that enlargement of the submandibular salivary glands in acromegaly is a relatively common clinical finding although it is not widely known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Few data reported the possible involvement of the salivary glands in acromegaly. Thomson et al . (1974), in a study performed with 99m Tc scintiscan and sialography in three patients, suggested that Acro patients had an increase of submandibular salivary gland volume.…”
Section: Discussionmentioning
confidence: 99%
“…Few data reported the possible involvement of the salivary glands in acromegaly. Thomson et al . (1974), in a study performed with 99m Tc scintiscan and sialography in three patients, suggested that Acro patients had an increase of submandibular salivary gland volume.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, not only dental components are modified by GH and IGF-1 excess but also soft tissue may be involved in facial changes due to acromegaly. In fact, it has been found that acromegalic patients commonly have enlarged submandibular glands (regardless of the activity of the disease) [31][32][33], though the parotid is rarely affected [34]. Glandular function is generally not compromised in these cases, and the pathophysiology related to these manifestations is not clear [34,35].…”
Section: Oral Manifestations and Maxillo-facial Featuresmentioning
confidence: 99%